A case of pulmonary arterial hypertension complicated by anti-neutrophil cytoplasmic antibody-associated vasculitis and systemic sclerosis. Issue 4 (2nd October 2021) - Yoshifuji, Hajime; Kagebayashi, Sumika; Kinoshita, Hideyuki; Fujii, Takao; Okano, Yoshiaki; Katsushima, Masao; Mimori, Tsuneyo
Abstract: Pulmonary arterial hypertension (PAH) is a rare complication of ANCA-associated vasculitis (AAV). We report a 37-year-old man with PAH complicated by both AAV and SSc who presented with dyspnea, cardiac enlargement, positive myeloperoxidase (MPO)-ANCA, anti-centromere antibodies, proteinuria, and urinary casts. Elevated pulmonary arterial pressure (58/22/34 mmHg) and low PAWP (2 mmHg) were confirmed by right heart catheterization. Treatment with glucocorticoids (GC) decreased urinary protein and serum MPO-ANCA; however, PAH did not respond to GC. Therefore, a combination of beraprost, bosentan, and tadalafil was needed. The differences in responses to GC suggest that the pathophysiology of nephropathy is different from that of PAH. We considered that nephropathy was associated with AAV but that PAH was associated with SSc in the present case. We discuss the pathophysiology and treatment response of PAH complicated by AAV, referring to nine past cases.